Investor behavior towards IPOs in Kenya: An Empirical Evaluation of the Factors influencing Investor Behavior in Kenya - Owiye , O. P. (Advances in Social Sciences Research Journal, 2020)
The period 2000-2013 witnessed a tremendous rise in investor participation in IPOs in Kenya. A number of IPOs have resulted in over-subscription. Outstanding cases include; Kenya-Re (334%), Kengen (236%), Eveready (800%), Safaricom (363%), Mumias Sugar (200%), Access Kenya (300%), Scan Group (520%) and Telkom (300%). The purpose of this study was to empirically investigate factors influencing investor behavior towards IPOs in Kenya. The study had, as its target population people residing in Kenya who have previously participated in any one or more of the following IPOs; Mumias Sugar, Safricom, Kengen, Telkom, Eveready, Kenya- Re, Access Kenya, and Scan Group. Simple Random Sampling was used to select a sample of respondents from the target population. Factor Analysis was used to analyze data collected from the respondents to generate understanding of the main motivation to the hightened interest in IPOs by investors. A number of factors thought to be driving investor’s interests towards initial public offers in Kenya were identified. These factors were conveniently categorized into three in order of significance, general state of the economy, confidant’s opinions, and leading communication from government sources.